Key success factors for quality management implementation: evidence from the public sector. (2nd September 2016) - Pimentel, Luís; Major, Maria
Abstract : The purpose of this paper is to identify the crucial factors for the successful implementation of a quality management/total quality management (TQM) process, particularly in the public sector. The paper adopts an explanatory longitudinal case study, using case research design to support the investigation. The case study consists of three government agencies where the results and outcomes of a quality management programme differed. This programme was launched by a specific ministry in Portugal, linked to organisational change and delivering excellence. The study was built on quality management literature, highlighting the contributions of J. S. Oakland [(2004). Oakland on quality management . Oxford: Elsevier Butterworth-Heinemann] and J. Oakland [(2011). Leadership and policy deployment: The backbone of TQM. Total Quality Management & Business Excellence, 22 (5), 517–534]. The key findings of the paper show that the main items delivering excellence, identified in the 'Oakland TQM model' (the 4Ps and the 4Cs), primarily explain the different perceptions of results and outcomes. The investigation also identified other factors that can help account for successful implementation of quality management, such as 'power' and 'collective involvement'. Consequently, a refined 'Oakland TQM model' is proposed, as well as a visualisation of the interaction of the items/factors involved in an input/output perspective.